Pelatihan Peningkatan Kompetensi Guru Madrasah Aliyah dalam Merancang dan Menerapkan Strategi Pembelajaran Diferensiasi Kurikulum Merdeka di Kabupaten Lima Puluh Kota - Hasanuddin WS, Hasanuddin WS; Zulfadhli, Zulfadhli; Emidar, Emidar (Universitas Negeri Padang, 2025)
This program aims to improve teachers' abilities in designing and implementing differentiated learning strategies and developing insights into how to organize a learning process that is truly student-centered, each with its own unique character and personality within the classroom.The differentiated learning model is one of the recommended learning models for classroom implementation, and is a requirement of the Independent Curriculum (Curriculum Merdeka) that teachers must implement. Furthermore, this activity focuses on improving understanding of the planning, implementation, and evaluation procedures for learning that are oriented toward student success in completing the Independent Curriculum program.This training activity utilizes problem-solving methods, case studies, and project-based training (which requires the production of a final product in the form of a lesson plan for Indonesian Language subjects using the collaborative learning model and differentiated learning strategy.